Implementation Of Health Protocols For Traders In Kotabaru Market As An Effort To Prevent The Transmission Of Covid-19 In 2022: Penerapan Protokol Kesehatan Pada Pedagang Di Pasar Kotabaru Sebagai Upaya Pencegahan Penularan Covid-19 Tahun 2022) - Irma Sari; Firman Edigan; Herniwanti Herianto; Syukaisih Syukaisih (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Health protocols are a series of rules issued by the government through the Ministry of Health in regulating the safety of activities during the COVID-19 From the results of the initial survey conducted in the Kotabaru market, many traders and buyers did not follow health protocols such as wearing masks, washing hands and maintaining distance as well as the unavailability of facilities for hand washing in the market area. This study aims to determine the implementation of health protocols in the Kotabaru seberida market Kec. Keritang Kab. Inhil Prov. Riau. This type of research is descriptive qualitative by using observation methods and in-depth interviews, namely to trader, buyers, kotabaru seberida village staff and market managers. The results showed that the implementation of health protocols in the Kotabaru market has not been optimal. Suggestions are expected to the Kotabaru Seberida Village government to form a COVID-19 prokja team and periodically check the implementation of health protocols, for traders and buyers to always implement health protocols, for market administrators to ensure the availability of facilities in the market and for related health agencies to continue to carry out health protocol promotions in the Kotabaru market.